New Chemical Treatment for Permanent Removal of Condensate Banking from Different Gas Reservoirs - Hassan, Amjed (ACS Omega, 2019)
[Image: see text] Condensate banking represents a challenging problem in producing the hydrocarbon from tight gas reservoirs. The accumulation of liquid condensates around the production well can significantly impair the gas flow rate. Gas injection and hydraulic fracturing are the common techniques used to avoid the condensate development by maintaining the reservoir pressure above the dew point curve. However, these treatments are associated with high operational costs and large initial investment. This study presents a new chemical treatment for removing the condensate banking using thermochemical solutions. The presented treatment can cause a permanent impact on the treated formations. Chemicals are injected to react downhole and generate in situ pressure and heat in certain conditions. The generated pressure can raise the gas pressure above the dew point, and the generated heat can change the phase of the liquid condensate to gas. Kinetic analysis indicates that thermochemical fluids can increase the temperature and heat by 85 °C and 369 kJ/mol, respectively. In addition, the impact of clay content on the efficiency of thermochemical treatment was studied using coreflooding experiments. A condensate removal of more than 60% was achieved using the huff and puff injection mode. A good correlation between the rock permeability and the condensate removal efficiency was observed. Higher condensate removal was obtained for the rock samples with high permeability values. Moreover, the presence of clay minerals in the treated rock showed a minor impact on the condensate removal, indicating that the injected chemicals are able to stabilize the clay minerals and avoid clay damage. This research shows that thermochemical treatment can remove more than 60% of the condensate damage for different types of tight sandstones. Huff and puff treatment was found to be a very practical approach to diminish the condensate banking from different sandstone rocks. Also, this work confirms that thermochemical treatment can be applied in the clayey formation for removing the condensate blockage without affecting the clay stability or inducing clay damage. Ultimately, this study introduces a new chemical treatment in the gas industry, and the used chemicals are effective, environmentally friendly, and not expensive.